Dampak Positif dan Negatif Pembelajaran Online Terhadap Siswa SMA Masa Pandemi - Sapri; Reno Supardi; Dian Mardiati Sari; Rizka Tri Alinse; Annisa Putri Pratiwi (Jurnal Garuda Pengabdian Kepada Masyarakat, 2023)
In this online learning there are many obstacles, especially on assignments that are too many and do not match the material optimally so that students experience difficulties and end up stressed. This is experienced by many students who already look bored with this pandemic situation, in addition to boredom, many students have difficulty while studying, mental disorders will also affect the condition of students to be more sensitive to their daily environment. The atmosphere when children look bored or bored in carrying out online learning of course requires support from parents and families because to stabilize the condition of students, the atmosphere at home must be more conducive when online learning takes place. Online learning has both positive and negative impacts.